RANCANG BANGUN APLIKASI MONITORING PENCAPAIAN KINERJA KEPALA SEKOLAH DASAR BERBASIS WEB PADA LEMBAGA PENJAMINAN MUTU PENDIDIKAN - Hergantoro, Firman Anom; Hariadi, Bambang; Shintawati, Rahayu Arya (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
The develop Design of Web-Based Monitoring Application of the Achievement of Primary School Principals on Lembaga Penjaminan Mutu Pendidikan (LPMP) Jawa Timur use waterfall method., can display the results of the performance of principal report in all eastern Java and an evaluation form on the training if the value of the performance of the principal each competency is not eligible. The trials’ result concludes that the monitoring application of principals achievement is able to display reports the performance of the principal in implementing the six competencies of performance of each town, county, down to the level of the principal itself.